Overcoming chemoresistance in mucinous adenocarcinoma: the impact of tumor microenvironment and genetic alterations - Pandi, Kaniga; Binoy Varghese Cheriyan; Vishali Ramesh; Sowparnika Murugavel; Jaya Surya Venkatesan (Creative Pharma Assent, 2025)
Background: Mucinous adenocarcinoma (MAC) is a rare, aggressive subtype of adenocarcinoma, distinguished by excessive extracellular mucin production. This feature impairs drug penetration and contributes to poor chemotherapy response and chemoresistance. Genetic mutations (e.g., KRAS, BRAF, PI3K/AKT), epithelial-to-mesenchymal transition (EMT), alterations in the tumor microenvironment, and mucin barriers contribute to this resistance. Objective: This narrative review aims to comprehensively summarize the molecular and microenvironmental mechanisms behind chemoresistance in MAC and highlight emerging therapeutic strategies to overcome it. Results: Chemoresistance in MAC arises from oncogenic signaling, immune evasion, hypoxia, and mucin-mediated drug exclusion. Promising approaches include mucolytic agents, small-molecule inhibitors, immune checkpoint inhibitors, RNA-based therapies, and nanoparticle-assisted drug delivery. Precision medicine, which utilizes genomic and transcriptomic profiling, is advancing individualized treatment; however, clinical translation remains limited. Conclusion: Resistance in MAC stems from both genetic and microenvironmental factors. Understanding these mechanisms is crucial for developing more effective, personalized therapies to improve patient outcomes. Future efforts should focus on validating novel therapies through clinical trials, discovering predictive biomarkers, and exploring tumor heterogeneity with multi-omics technologies. Integrating targeted therapies with advanced delivery systems may offer significant advances in treating chemoresistant MAC.